Numerical Simulation of Shock Wave Diffraction Using the Wall Ghost Immersed Boundary Method - Jianxin ZHANG; Hong CHEN; Conglin LIU; Ge WANG (气体物理)
In the previously developed ghost fluid methods (GFMs), the focus is often on the fluid-fluid interface. Based on this method, a ghost immersed boundary method for investigating complex shock-obstacle interactions with strong discontinuity was presented. The values of the fluid variables at the embedded ghost-cells were obtained using a local Riemann problem solver that involves the neighboring ghost nodes. The method was then implemented within an HLLC scheme to simulate the complex fluid-solid interactions. Several test cases were presented to validate the proposed scheme. The developed solver was first validated against the experimental results of supersonic flow past a circular cylinder and step with 90° corner, then the results of shock/triangular prism interaction were further compared with the experimental results of literature. Excellent agreement is obtained in terms of compressible wave propagation, as well as vorticity development and transport. The method has good applicability for studying wave evolution in the early stage of shock wave impact on obstacles.